2021
DOI: 10.1051/0004-6361/202039809
|View full text |Cite
|
Sign up to set email alerts
|

A preserved high-z compact progenitor in the heart of NGC 3311 revealed with MUSE 2D stellar population analysis

Abstract: Context. Massive early-type galaxies are believed to be the end result of an extended mass accretion history. The stars formed in situ very early on in the initial phase of the mass assembly might have originated from an extremely intense and rapid burst of star formation. These stars may still be found within the cores of such galaxies at z = 0, depending on their accretion and merger histories. Aims. We wish to investigate the presence of a surviving high-z compact progenitor component in the brightest galax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 150 publications
3
20
1
Order By: Relevance
“…In addition to the internal dynamics of galaxies within Fornax, the gas in the cluster is found to be shock heated at a temperature of κT = 1.48 keV (Frank et al 2013), which would also prevent fueling of cool gas and thus star formation. This interpretation is in agreement with the recent measurements of similarly positive [Mg/Fe] gradients in some nearby cluster galaxies (Ferreras et al 2019;Barbosa et al 2021a).…”
Section: On the Chemical Enrichmentsupporting
confidence: 93%
“…In addition to the internal dynamics of galaxies within Fornax, the gas in the cluster is found to be shock heated at a temperature of κT = 1.48 keV (Frank et al 2013), which would also prevent fueling of cool gas and thus star formation. This interpretation is in agreement with the recent measurements of similarly positive [Mg/Fe] gradients in some nearby cluster galaxies (Ferreras et al 2019;Barbosa et al 2021a).…”
Section: On the Chemical Enrichmentsupporting
confidence: 93%
“…The comparison with the E-MILES is relevant because these models are widely used in the study of intermediate and old stellar populations (Neumann et al 2021;Rodriguez Beltran et al 2021;Barbosa et al 2021;Lonoce et al 2021, to name a few recent works). Here, we use the E-MILES models calculated using the Salpeter IMF and both the Padova00 and BaSTI (Pietrinferni et al 2004(Pietrinferni et al , 2006Cordier et al 2007;Percival et al 2009) isochrones.…”
Section: General Behaviour Of the Modelsmentioning
confidence: 99%
“…Several other works, studying the light distribution and the kinematics of the Hydra I cluster core, demonstrated that the mass assembly is still active around NGC 3311, and showed the presence of ongoing interactions between galaxies (Arnaboldi et al 2012;Ventimiglia et al 2011;Hilker et al 2018;Barbosa et al 2018Barbosa et al , 2021Koch et al 2012). Hereafter, we assume that the cluster center is represented by NGC 3311: R. A.…”
Section: Introductionmentioning
confidence: 97%